DEVELOPMENT OF A PRE-IMPACT DYNAMICS SIMULATOR FOR A VEHICLE INVOLVED IN A ROAD ACCIDENT - Gomes, Luís Miguel Marques (2024)
This Master's thesis in Automotive Engineering focuses on the development of a Pre-Impact Dynamics Simulator (PIDS) for vehicles involved in road accidents. In response to the latest European Union (EU) regulation mandating Event Data Recorders (EDR) in all passenger cars and goods vehicles up to 3.5 tonnes circulating in EU since 2022, this report explores how EDR data can enhance the understanding of vehicle trajectories before collisions, i.e., the pre-impact trajectories of vehicles involved in road accidents, thereby contributing to increased rigour and accelerating road accident investigations. The PIDS integrates pre-impact data extracted from EDRs with vehicle dynamics models, providing reliable reconstructions of pre-impact trajectories. To complement the interpretation of the simulator's results, this Master’s thesis also includes a comprehensive scientific review of vehicle dynamics, drivers’ behaviours in pre-impact situations, and advanced driver assistance technologies (ADAS). Furthermore, it examines methodologies for reconstructing vehicle collisions at accident sites, with a particular focus on existing kinematic methods and data collection tools. The validation of the PIDS results was conducted using AVL VSM™ software and it was also applied to real-world case studies, highlighting its effectiveness in accurately reconstructing pre-impact trajectories across various scenarios. The findings underscore the simulator’s potential to significantly improve the efficiency and rigour of road accident reconstructions, providing valuable insights for legal, engineering, and road safety applications. This Master’s thesis ends with recommendations for future enhancements to the PIDS, focusing on the use of more complex vehicle dynamics models and the implementation of alternative methods for measuring vehicle speed under rollover conditions.